Caracterização ambiental e hidrológica da bacia do córrego Barbado em Cuiabá-MT - Ventura, Rosangela Maria Guarienti (2011)
The increasing urbanization without the had planning of the cities propitiates a process of disordered occupation that results, in general, in invasions of areas of ambient protection and risk, with: burial of springs, waterproofing of green areas, solid degradation of the edges and the bodies of water through the launching of effluent liquids and residues. Whose consequence provoke alterations in the natural water regimen of the basins and deterioration of the quality of waters. These aspects if have become excellent in the studies of urban basins, as it is the case, of the basin of the Bearded stream that is inserted in the urban perimeter of Cuiabá, MT. Structural solutions that exist just transfer the problem of disposing to the mouth, creating pieces of critical points that come to overflow in heavy rains. With the objective to characterize ambiently and to analyze the hydrological elements of the basin, hypotheses had been considered as: if the physiography is inclined the flood; if the occupation dynamics is adjusted; if the profile of the occupants contributes for the degradation of the basian stream; if viability exists technique for application of measures of control in the basin; if it is possible to work with monitoring of quota and esteem of outflow for the verified quota; e if has as to relate the rain intensity with the outflow. To test these hypotheses, a section of the course of water was monitored, treated digital images and registers of socioeconomic and ambient had been analyzed. The study it resulted in: the stage discharge curve section, and hydrographs, hietograms, physiographic features, use map and occupation of land, estimate of sanitation coverage and profile of the occupants. The discharge curve allowed to relate the quotas registered in linigraph with the calculated outflow, producing hydrographs that illustrate water answers in the section of study for a rain event. The physiographic not adds characteristics of basins prone to flooding, however the format narrow and elongated provides a fast flow which combined with an impermeable area of 57.4% maximizes flood peaks. In classification of satellite pictures of the year 2009, it was estimated that 16.64% of basin area is composed of masonry, 26.16% concrete and 14.6% floor, areas that contribute to runoff. This study sample that the impacts of the current picture can be minimized, and some reversible ones, through the recovery of the green areas, structural improvements in the sanitation covering, interventions and work of ambient education with the inhabitants. The results of the hydrology survey can assist in projects of local workmanships that can brighten up the impact of the full ones and esteem the interference of mitigation measures in the water body.